Global Chinese (De Gruyter, 2015)
Global Chinese responds to the fast-growing scholarly interests in Chinese as a global language and offers a unique venue for original, ground-breaking studies of Chinese and its users in different geographical, historical and professional contexts. The journal publishes original research articles as well as debates, short notes, book reviews and regional profiles. The languages of publication are English and Chinese, with bilingual synopsis.